A Survey on Gruss-Type Inequalities by Means of Different Generalized Fractional Integrals - Jha, Shamvu; Bhatta, Chet Raj (Journal of Advanced College of Engineering and Management, 2022)
In this survey paper, we review a generalization of Gruss - type inequality by means of two different operators, one through K - fractional integral and other through Katugampola fractional integral. We state some related theorems, corollaries and their proofs. We study how results are interrelated?